Identification of environmental Vibrio cholerae non 01 non 139 by MALDITOF MS - Cuneo, Alejandra E. (2023)
Most Vibrio species identification methods take many days to deliver results, therefore it is important that research can be done on rapid and accurate detection and identification techniques. MALDI-TOF MS has proven to be a simple tool to identify and differentiate pathogens. The objective of this research was to recognize the available bibliographic information on the identification of Vibrio cholerae species non 01 non 139 of environmental origin by MALDI TOF MS. The Vibrio genera includes more than thirty species found in aquatic environments, some species cause diseases in both marine and human species. One of these organisms is V. cholerae, one of the most important species due to the production of cholera toxin (CT) which interrupts the transport of ions in the cells of the intestinal epithelium. The number of case reports involving V. cholerae no 01 no 139 in extraintestinal infections and potentially fatal bacteremia in healthy patients has increased and, despite the existence of molecular identification techniques such as PCR, sequencing, and gel electrophoresis pulsed-field, the MALDI TOF MS technique has been gaining ground in bacteriology laboratories in hospitals due to its speed and ease of use. There are studies that cover the detection of V. cholerae in MALDI-TOF MS, focusing on food and environment, however, when performing the search key, no specific studies on the detection of V. cholerae non 01 non 139 of environmental origin by MALDI TOF MS were found with the exception of a case report, presence in blood isolates, reviews of reports that indicate the importance of these microorganisms in the cause bacteremia and the importance of this technique for the future of bacterial identification. Therefore, is recognized that there is a need to continue producing new information to contribute to the implementation of genomic surveillance capable of predicting future epidemic outbreaks.